Voluntary Disclosure in the Annual Reports of Financially Distressed Companies in Indonesia - Wijantini Wijantini (Gadjah Mada International Journal of Business, 2006)
This paper examines voluntary disclosure in the annual reports of financially distressed companies in Indonesia. The disclosure score range is between 3 percent and 49 percent with the mean and median score of 25 percent and 26 percent, respectively, at the onset of distress. The score is measured as the ratio of the total items disclosed to the maximum possible items score applicable to the firm. The most disclosed items are in the category of financial highlights and general corporate information whereas the three least disclosed items concern projections, liquidity, and research and development. Moreover, the results of this study reveal that the level of voluntary disclosure in the financially distressed firms is higher than that in non-financially distressed firms. There is no significant difference between the types of information disclosed by the 2  groups. The statistical tests are applied for various years. Consistent with findings in previous studies, the size of the firm appears to be a positive variable significantly affecting the disclosure level.